Creating an environment for active, relational learning and teaching educational sociology in large classes - Hogan, V; Daniell, L (Informit, 2012)
The article offers information on a research that presents a model for effective learning and teaching at large classroom while encouraging active students' participation and deep learning in New Zealand. It is mentioned that the research explores the study of sociology and analyzes the role of scholarship in teaching and learning. Additionally, regular feedback from students were encouraged to improve teaching methodology at classrooms.
Keywords: Learning & teaching; Large classes; Active engagement; Deep learning; Sociology